DESAIN DAN EVALUASI PEMBELAJARAN STEAM PADA MATERI PEMISAHAN CAMPURAN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIVITAS SISWA DI SMAK SINT CAROLUS KUPANG - Fransiskus Gerlan; Maria Benedikta Tukan; Faderina Komisia (Universitas HKBP Nommensen, 2026)
STEAM (Science, Technology, Engineering, Art, and Mathematics) learning is an integrated learning model that encourages students to think critically and independently. This study aims to determine the implementation of STEAM learning and students’ learning outcomes on the topic of mixture separation. This research employed a descriptive method with a One Shot Case Study design. The sample consisted of all 11th-grade students of SMAK Sint Carolus Kupang, totaling 16 students, selected using a saturated sampling technique. The research instruments included observation sheets to assess the implementation of learning and tests to measure students’ learning outcomes based on knowledge (KI-3) and skills (KI-4) aspects, referring to the minimum mastery criteria (KKM).The results showed that the implementation of STEAM learning was categorized as good, with an average score of 4.00. Students’ learning outcomes also achieved mastery, with an average score of 86, exceeding the KKM standard. However, this study is limited by the small sample size and the absence of a control group. Therefore, future research is recommended to use a more robust experimental design with a larger sample size.